Forward-backward correlations and charged-particle azimuthal distributions in pp interactions using the ATLAS detector - Onofre, A. (2012)
Using inelastic proton-proton interactions at s√=900 GeV and 7 TeV, recorded by the ATLAS detector at the LHC, measurements have been made of the correlations between forward and backward charged-particle multiplicities and, for the first time, between forward and backward charged-particle summed transverse momentum. In addition, jet-like structure in the events is studied by means of azimuthal distributions of charged particles relative to the charged particle with highest transverse momentum in a selected kinematic region of the event. The results are compared with predictions from tunes of the pythia and herwig++ Monte Carlo generators, which in most cases are found to provide a reasonable description of the data.